Tinjauan Ghibah (Gosip) Menurut Syekh Nawai dalam Tafsir Marah Labid - Muhyi, Asep Abdul; Islamy, Mohammad Rindu Fajar (Attractive : Innovative Education Journal, 2022)
The purpose of this research is to find out Shaykh Nawawi al Bantani's interpretation of backbiting in Tafsir Marah Labid as well as to know the concept of backbiting according to Shaykh Nawawi Al-Bantani in Tafsir Marah Labid. This research uses the descriptive method of analysis. The object in this research is in the form of a written work entitled Tafsir Marah Labaid by Imama Nawawi, as for the focus of the research is the interpretation of verses of the Qur'an that are vilified with slander. Shaykh Nawawi al-Bantani understands the verse of slander, both in terms of language and terminology. When interpreting Surah al-Nur [24]: 11 Shaykh Nawawi understood backbiting with the word al-Ifku, which is a lie and a lie, meaning a person who brings false news. Shaykh Nawawi understood the behavior of slander by interpreting the verse with the narrations of the hadiths that narrate the people who commit slander also tell about the impact and torment of slander. So it can be understood that Shaykh Nawawi understood the verses of slander by using the interpretation of bil al-matsur with various narrations of hadith. As for the concept of slander in Tafsir Marah Labaid by Shaykh Nawawi al-Bantani, among others: Talking about someone unknown to him, Being prejudiced by the actions or actions of someone who is uncertain, Looking for and discussing other people's faults, Slander is the same as harming life someone, Ghibah is the same as slandering another person. Keywords: Ghibah Review, Interpretation Marah Labid, Syekh Nawawi Opinion